Disparities in the change of cervical cancer mortality rate between urban and rural Chiang Mai in the era of universal health care and the Thai national screening program - Patumrat Sripan; Imjai Chitapanarux; Ekkasit Tharavichitkul; Pooriwat Muangwong; Donsuk Pongnikorn; Narate Waisri; Chirapong Hanpragopsuk; Puttachart Maneesai; Panrada Tansiri; Malisa Poungsombat; Varunee Khamsan (BMC, 2021)
Abstract Background The Ministry of Public Health of Thailand established universal health coverage (UHC) in 2002, which also included national-level screening for cervical cancer in 2005. This study examined the changes in mortality of cervical cancer in rural and urban areas in Chiang Mai Province of northern Thailand during the era of UHC and the immediately preceding period. Methods Data of cervical cancer patients in Chiang Mai in northern Thailand, who died from 1998 through 2012, were used to calculate the change in age-standardized rates of mortality (ASMR) using a joinpoint regression model and to calculate estimated annual percent changes (APC). The change in mortality rate by age groups along with changes by geographic area of residence were determined. Results Among the 1177 patients who died from cervical cancer, 13(1%), 713 (61%) and 451 (38%) were in the young age group (aged < 30), the screening target group (aged 30-59) and the elderly group (aged ≥60), respectively. The mortality rate among women aged 30-59 significantly declined by 3% per year from 2003 through 2012 (p < 0.001). By area of residence, the mortality rate in women targeted by the screening program significantly decreased in urban areas but remained stable in more rural areas, APC of − 7.6 (95% CI: − 12.1 to − 2.8) and APC of 3.7 (95% CI: − 2.1 to 9.9), respectively. Conclusion The UHC and national cervical cancer screening program in Thai women may have contributed to the reduction of the mortality rate of cervical cancer in the screening target age group. However, this reduction was primarily in urban areas of Chiang Mai, and there was no significant impact on mortality in more rural areas. These results suggest that the reasons for this disparity need to be further explored to equitably increase access to cervical cancer services of the UHC.